Principles of computer architecture - Murdocca, Miles (Prentice Hall, 2000)
Designed especially for undergraduates in computer-related disciplines, with emphasis to support the compiler, operating system, and networking courses. For a first course in computer architecture or computer organization. This text covers computer architecture at the instruction set architecture (ISA) and system design levels. Starting with foundation material on data representation and computer arithmetic, the book moves through the basic components of a computer architecture, covering topics at increasing levels of complexity up through CISC, network architecture, and parallel architecture. The authors have adopted the use of a SPARC-subset for an instructional ISA called "ARC" (A RISC Computer), which is carried through the mainstream of the book, and is complemented with platform-independent software tools that simulate the ARC ISA as well as the MIPS and x86 (Pentium) ISAs.